TREATMENT OF OSTEOARTHRITIS IN ADOLESCENTS AND CRITERIA OF ITS EFFICIENCY - Shevchenko, N. S.; Lebets, I. S.; Matvienko, O. V.; Nelina, I. M.; Kashkalda, D. A. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
The article presents the results of research on the treatment of the initial stages of osteoarthritis (OA) in adolescence. There has been developed therapeutic complexes of differential treatment of this disease in adolescence. It provides complex use of chondroprotective, anti-inflammatory agents and drugs to improve microcirculatory disorders. The analysis of the effectiveness of the treatment in 59 adolescents with OA aged 12–18 years, of which females were 32 (54,23 %), male — 27 (45,76 %) has been conducted. The disease developed on the background of hypermobility syndrome (HMS) in 18, on the background of reactive arthritis (ReA) — in 16 people. The efficiency of the proposed methods was estimated at three levels of observation: the end of the first period in the hospital, at 1 year and 2–3 years. It has been established that positive result of the above complexes of treatment is 56,2 %.